2010
DOI: 10.1002/mc.20607
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutant lung cancer cells are differentially responsive to MEK inhibitor due to AKT or STAT3 activation: Implication for combinatorial approach

Abstract: KRAS is frequently mutated in nonsmall cell lung cancer (NSCLC), resulting in the activation of the MAPK/ERK kinase (MEK)/ERK pathway. High-throughput mutation profile has shown that lung cancer frequently harbors comutation of cancer-related genes. Therefore, given that cancer cells have multiple genetic alterations, combinatorial therapeutic strategy is demanded for effective cancer therapy. To address this, we first characterized MEK dependence in four NSCLC cells. Two cells (H358, A549) carried KRAS mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 41 publications
5
81
0
Order By: Relevance
“…10,14,[18][19][20][21][22][23] AZD6244 is a benzimidazole and selective 2nd generation MEK inhibitor with reported activity at nanomolar concentrations against purified MEK1 enzyme in preclinical solid tumor studies. [18][19][20][21][22][23] Further, AZD6244 is a noncompetitive MEK inhibitor with preclinical antitumor activity in solid tumor models including hepatocellular, colon, myeloma, thyroid, pancreatic, melanoma, and breast cancers 19,20,41 and tested clinically in phase 1 24 and phase 2 trials of advanced, refractory colorectal, melanoma, and lung cancer. [25][26][27] AZD6244 has been examined in leukemia and myeloma models, [42][43][44] however to our knowledge, has never been tested in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,14,[18][19][20][21][22][23] AZD6244 is a benzimidazole and selective 2nd generation MEK inhibitor with reported activity at nanomolar concentrations against purified MEK1 enzyme in preclinical solid tumor studies. [18][19][20][21][22][23] Further, AZD6244 is a noncompetitive MEK inhibitor with preclinical antitumor activity in solid tumor models including hepatocellular, colon, myeloma, thyroid, pancreatic, melanoma, and breast cancers 19,20,41 and tested clinically in phase 1 24 and phase 2 trials of advanced, refractory colorectal, melanoma, and lung cancer. [25][26][27] AZD6244 has been examined in leukemia and myeloma models, [42][43][44] however to our knowledge, has never been tested in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 ARRY-142886 (AZD6244, selumetinib; Astra Zeneca) is a selective nonATP-competitive 2nd generation oral MEK inhibitor studied primarily in solid tumor studies with reported nanomolar activity against purified MEK1 enzyme. [18][19][20][21][22][23] Furthermore, phase 1 and phase 2 solid tumor clinical trials have shown this agent to be well-tolerated and have encouraging clinical efficacy. [24][25][26][27] To our knowledge, minimal data are available on newer generation MEK inhibitors in lymphoma and moreover, this anti-MEK agent has never been examined in lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…The ligand binding-induced dimerization results in cross-autophosphorylation of key tyrosine residues in the cytoplasmic domains, which function as docking sites for downstream signal transducers. 36 This activation of EGFR initiates signaling cascades involving several downstream pathways, which induce crucial cellular responses, such as proliferation, differentiation, motility, and survival 13,[52][53][54][55][56][57][58][59][60][61][62] (Figure 1).…”
Section: Egfr Mutationsmentioning
confidence: 99%
“…56,216 The histological phenotype of BRAF mutant adenocarcinomas has not been well described, but was reported to be a mixed type adenocarcinoma with a high incidence of papillary (80%) and lepidic growth (50%) patterns. 217 De Oliveira Duarte Achcar et al 218 investigated 15 primary micropapillary lung adenocarcinomas for KRAS, EGFR, and BRAF mutations.…”
Section: Braf Mutationmentioning
confidence: 99%
“…The dual inhibition of MEK and EGFR or MEK and signal transducer and activator of transcription 3 (STAT3) signaling pathways may constitute a potent therapeutic strategy for the treatment of KRAS mutant NSCLCs. But AZD6244 displays insufficient efficacy in non-small cell lung cancers (NSCLCs) due to deregulated expression and/or mutations of PIK3CA and PTEN [59][60][61][62][63]. A rational basis has been validated for choosing the inhibitor to best combine with the MEK inhibitor in cells on the basis of the expression and mutations of several oncogenes [64][65][66][67][68][69][70][71][72][73][74].…”
Section: The Applications Of Components Of Raf-mek-mapk Pathway In Anmentioning
confidence: 99%